4(R/S)-Guanidinylprolyl collagen peptides: on-resin synthesis, complexation with plasmid DNA, and the role of peptides in enhancement of transfection - Nanda, Manaswini; Ganesh, Krishna N. (Journal of Organic Chemistry, 2012)
Chimeric collagen peptides containing cationic 4(R/S)-guanidinylproline are synthesized by in situ amidinylation of 4(R/S)-aminoproline residues. These peptides uniquely enhance the transfection efficiency of GFP-encoded plasmid DNA (pRmHa3-GFP) into cells through efficient DNA condensation resulting from nonspecific electrostatic interactions of cationic guanidino groups and localize in subcytoplasmic organelles.